2022
DOI: 10.1002/pol.20220131
|View full text |Cite
|
Sign up to set email alerts
|

Chemically recyclable crosslinked thiol‐ene photopolymers via thiol‐disulfide exchange reactions

Abstract: Conventional crosslinked photopolymers possess permanent network structures, which cannot be remolded/recycled and generally discarded as waste after use. Research has begun to incorporate dynamic bonds into crosslinked photopolymers to make them reprocessable/recyclable, however, previous studies typically require tedious pre‐syntheses to obtain photoreactive building blocks that contain desired dynamic linkages/functionalities. In this study, we report a simple, one‐step, and scalable synthesis of chemically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 61 publications
1
16
0
Order By: Relevance
“…Wang et al demonstrated this approach on an epoxy polymer cured with mixtures of disulfide-containing and disulfide-free carboxylic acids at varying proportions. Most recently, Alfarhan et al studied disulfide-containing thiol–ene networks and their depolymerization via base-catalyzed thiol–disulfide exchange that yields repolymerizable thiol oligomers …”
mentioning
confidence: 99%
“…Wang et al demonstrated this approach on an epoxy polymer cured with mixtures of disulfide-containing and disulfide-free carboxylic acids at varying proportions. Most recently, Alfarhan et al studied disulfide-containing thiol–ene networks and their depolymerization via base-catalyzed thiol–disulfide exchange that yields repolymerizable thiol oligomers …”
mentioning
confidence: 99%
“…The resulting mixture was stirred overnight at room temperature to undergo network deconstruction via base-catalyzed thiol-disulfide exchange reactions. 48 After ∼6 h, a homogeneous solution was obtained, which was then concentrated by rotary evaporation and vacuum dried at room temperature for 24 h to fully remove the volatile triethylamine and acetone.…”
Section: Methodsmentioning
confidence: 99%
“…S4 †) of the resulting decrosslinked materials confirmed the complete X Green network degradation via base-catalyzed thiol-disulfide exchange reactions (see ESI † for details), in a manner similar to that reported in our previous study. 48 Notably, these decrosslinked materials contain the same amount of [SH] groups as those in the original decrosslinking solution (since [SH] content remains constant after thiol-disulfide exchange), which can be recrosslinked with a stoichiometric amount of triacrylate monomers, if needed. 48 3.2.…”
Section: Polymer Chemistry Papermentioning
confidence: 99%
“…In a more recent example, Jin and coworkers reported a strategy based on commercially available monomers using the thiol-disulfide exchange to chemically recycle crosslinked thiol-ene photopolymers. 28 An obvious advantage of designing these photocrosslinked polymers is to circumvent the burden of developing resins with limited recyclability.…”
Section: Introductionmentioning
confidence: 99%